2011
DOI: 10.1128/aac.01571-10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Chlorhexidine Tolerance in Burkholderia cenocepacia Biofilms

Abstract: The high tolerance of biofilm-grown Burkholderia cepacia complex bacteria against antimicrobial agents presents considerable problems for the treatment of infected cystic fibrosis patients and the implementation of infection control guidelines. In the present study, we analyzed the tolerance of planktonic and sessile Burkholderia cenocepacia J2315 cultures and examined the transcriptional response of sessile cells to treatment with chlorhexidine. At low (0.0005%) and high (0.05%) concentrations, chlorhexidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 35 publications
(43 reference statements)
1
63
0
Order By: Relevance
“…The primary features of the A. baumannii chlorhexidine resistance response, i.e., up-regulation of genes encoding RND and PCE family efflux systems, are conserved in other γ-proteobacteria (9), as well as β-proteobacteria (10). Given the phylogenetic distance of these organisms, this similarity of regulatory responses to a compound that has only been synthesized since the early 20th century is intriguing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary features of the A. baumannii chlorhexidine resistance response, i.e., up-regulation of genes encoding RND and PCE family efflux systems, are conserved in other γ-proteobacteria (9), as well as β-proteobacteria (10). Given the phylogenetic distance of these organisms, this similarity of regulatory responses to a compound that has only been synthesized since the early 20th century is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the adeAB efflux transporter genes, only one gene was overexpressed by more than 10-fold in response to chlorhexidine exposure in A. baumannii, A1S_2063, which was annotated as encoding a hypothetical protein. Orthologs of A1S_2063 in P. aeruginosa and B. cenocepacia were also among the most overexpressed genes in response to chlorhexidine challenge (9,10). Therefore, these genes are a highly conserved component of a chlorhexidineresponsive regulatory circuit in several proteobacterial genera.…”
Section: A Small Hypothetical Membrane Protein Was Overexpressed Inmentioning
confidence: 97%
“…Chlorhexidine is an antiseptic that acts via membrane disruption. It was previously shown to lead to the upregulation of a number of pC3 genes in J2315, including the aforementioned chaperonin-encoding genes BCAS0637 and BCAS0638 (8-and 22-fold, respectively) (29). B. cenocepacia H111 showed very significantly higher resistance to 5% chlorhexidine than H111⌬c3 (P ϭ 0.006618; the mean zone of inhibition tested by disc diffusion assay was 5.2 mm for H111 and 6.2 mm for H111⌬c3, with a standard error of 0.2 in both cases).…”
Section: Resultsmentioning
confidence: 99%
“…The second general factor that would be expected to limit the occurrence of pC3-null communities in the environment is the importance of this replicon to stress tolerance and environmental fitness. Orthologs of the B. cenocepacia J2315 chaperonin genes BCAS0637 and BCAS0638, which were shown to be upregulated under various stresses (28,29), were found in several strains of the Bcc species B. cenocepacia, B. multivorans, and B. ambifaria by BLAST analysis. As a result of these factors increasing the stability of pC3 within the Bcc, this nonessential replicon is highly prevalent throughout the complex and (A) Bacteria were grown overnight in LB medium and then subcultured into LB supplemented with additional NaCl to a total concentration of 2 M. Viability was measured before inoculation into high-salt LB broth and after 2.5, 5, and 24 h of incubation at 37°C with shaking in this medium.…”
Section: Discussionmentioning
confidence: 99%
“…A bioinformatics study performed by Coenye et al (12) identified 213 putative sRNAs on the genome of the highly epidemic clinical isolate B. cenocepacia J2315 (13), although the expression of only 4 sRNAs was confirmed (12). In another study on the transcriptional responses of planktonic and sessile cells of B. cenocepacia J2315 upon exposure to chlorhexidine, 19 intergenic sequences putatively encoding sRNAs were identified as differentially expressed, although their biological function remains unknown (14). More recently, 24 sRNAs from B. cenocepacia J2315 were identified and validated, based on the exploitation of the RNA binding ability of Hfq (15).…”
mentioning
confidence: 99%